2015
DOI: 10.1186/s13023-015-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of adult pulmonary Langerhans cell histiocytosis: a prospective multicentre study

Abstract: BackgroundThe natural history of pulmonary Langerhans cell histiocytosis (PLCH) has been unclear due to the absence of prospective studies. The rate of patients who experience an early progression of their disease is unknown. Additionally, conflicting effects of smoking cessation on the outcome of PLCH have been reported.MethodsIn this prospective, multicentre study, 58 consecutive patients with newly diagnosed PLCH were comprehensively evaluated over a two-year period. Our objectives were to estimate the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 24 publications
2
93
1
10
Order By: Relevance
“…Previous study found that lung function deteriorated in 60% of the patients and improved in 20% (16). Serial lung function assessment is necessary for the follow-up of PLCH patients to identify their disease progression (28). However, in the current study, PFTs data during follow-up are not achieved, so a larger follow-up study is needed to prove the findings in the previous study (16).…”
Section: Discussioncontrasting
confidence: 39%
“…Previous study found that lung function deteriorated in 60% of the patients and improved in 20% (16). Serial lung function assessment is necessary for the follow-up of PLCH patients to identify their disease progression (28). However, in the current study, PFTs data during follow-up are not achieved, so a larger follow-up study is needed to prove the findings in the previous study (16).…”
Section: Discussioncontrasting
confidence: 39%
“…Obstructive, restrictive and mixed patterns have been described. In the early stages, pulmonary function testing may be normal in ∼10% of patients [13]. The most common abnormality is a reduction of DLCO, which is observed in 80-90% of cases and is primarily a reflection of pulmonary vascular dysfunction [13,14,23].…”
Section: Lung Functionmentioning
confidence: 99%
“…At clinical presentation [13,14], PLCH is diagnosed by three main symptoms. 1) Respiratory symptoms (cough and dyspnoea on exertion), which occur in approximately two-thirds of all such cases.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations